Delayed-Release Dimethyl Fumarate Safety and Efficacy in Pediatric Patients With Relapsing-Remitting Multiple Sclerosis - Alroughani, Raed; Huppke, Peter; Mazurkiewicz-Beldzinska, Maria; Blaschek, Astrid; Valis, Martin; Aaen, Gregory; Pultz, Joe; Peng, Xiaomei; Beynon, Vanessa (Frontiers in Neurology, 2021)
Background: Pediatric multiple sclerosis (MS) is rare: only 2–5% of MS cases are diagnosed before 18 years of age, and data on disease-modifying therapies (DMTs) for pediatric MS are limited. The CONNECTED study assessed the long-term safety and efficacy of treatment with delayed-release dimethyl fumarate (DMF), an oral MS DMT, in pediatric patients with MS. Methods: CONNECTED is the 96-week extension to FOCUS, a 24-week phase 2 study of patients aged 13–17 years; participants received DMF 240 mg twice daily. Endpoints included (primary) incidence of adverse events (AEs), serious AEs, and DMF discontinuations due to an AE, and (secondary) T2 hyperintense lesion incidence by magnetic resonance imaging and annualized relapse rate (ARR). Results: Twenty participants (median [range] age, 17 [14–18] years; 65% female) who completed FOCUS enrolled into CONNECTED; 17 (85%) completed CONNECTED. Eighteen participants (90%) experienced AEs: the most frequent was flushing (25%). None experienced infections or fever related to low lymphocyte counts. Three participants experienced four serious AEs; none led to DMF discontinuation. Twelve of 17 participants (71%) had no new/newly enlarged T2 lesions from week 16 to 24, two (12%) had one, and one each (6%) had two, three, or five or more lesions (median [range], 0 [0–6]). Over the full 120-week treatment period, ARR was 0.2, an 84.5% relative reduction (n = 20; 95% CI: 66.8–92.8; p < 0.0001) vs. the year before DMF initiation. Conclusions: The long-term safety and efficacy observed in CONNECTED was consistent with adults, suggesting pediatric and adolescent patients with MS might benefit from DMF treatment.